The Correlation Between Lipid Profile and Xanthelasma - Puridelko Kampar; Qaira Anum; Sri Lestari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Xanthelasma is an abnormal lipid deposition on palpebrae, which is observable as yellowish plaque or nodules. Its incidence is 0.56–1.5% with onset of 15–73 years old and mostly occurs in the fourth and fifth decade. Few reports of xanthelasma did not cover the correlation between lipid profile and xanthelasma in Indonesia. Purpose: To find a correlation between lipid profile with xanthelasma in Dr. M. Djamil Hospital, Padang. Methods: This was an analytic cross-sectional study with consecutive sampling. There were 36 participants (18 xanthelasma and 18 control). Result: The highest age group was >36 - ≤45 years old (38.89%). More cases were observed in female (66.67%). Body mass index examination of xanthelasma revealed that most were overweight (55.56%). Grade I xanthelasma was the most common (72.22%). The cholesterol serum level of xanthelasma patients was higher than the subject controls (224.61±29.77 mg/dl versus 169.39±35.84 mg/dl) (p<0,05). The High Density Lipoprotein (HDL)  serum level of xanthelasma patients was lower than controls (46.44±14.19 mg/dl versus 51.78±15.9 mg/dl) (p>0,05). The Low Density Lipoprotein (LDL) serum level of xanthelasma patients was higher than control (139.39±29.73 mg/dl versus 106.50±35.43 mg/dl) (p<0,05). Triglyceride serum level of xanthelasma patients was higher than the controls (167.83±87.26 mg/dl versus 121.61±54.52 mg/dl) (p>0,05). Conclusion: There was a correlation between higher cholesterol and LDL serum level with xanthelasma. No correlation between lower HDL and a higher triglyceride serum level with xanthelasma.